Physical exercise recommendations for patients with chronic myeloid leukemia based on individual preferences identified in a large international patient survey study of the East German Study Group for Hematology and Oncology (OSHO #97) - Hollenbach, Lina; Rogahn, Julia; le Coutre, Philipp; Schulze, Susann; Muegge, Lars-Olof; Geissler, Jan; Gruen, Julia; Junghanss, Christian; Felser, Sabine (Frontiers in Oncology, 2024)
Background: Tyrosine kinase inhibitors (TKIs) have significantly lowered mortality of chronic myeloid leukemia (CML) patients adjusting life expectancy to that of the standard population. However, CML and its treatment with TKIs causes a high disease burden. Physical exercise (PE) could be a non-pharmacological approach to reducing these and improving quality of life. Purpose: The aim of this study was to determine the individual disease burden as well as PE preferences of CML patients and to deduce thereof specific PE recommendations. Methods: This multicenter survey was conducted in cooperation with the LeukaNET/Leukemia-patient network including CML patients aged ≥18 years (German Registry of Clinical Trials, DRKS00023698). The severity of selected symptoms was assessed using the adapted Myeloproliferative Neoplasms Symptom Assessment Form: 0 (absent), 1–30 (mild), 31–70 (moderate), or 71–100 (severe). Information about patients’ PE needs and preferences depending on their motivation was recorded. Results: A total of 212 questionnaires were analyzed (52% female, median age 54 years). The prevalence of moderate-to-severe symptoms was 49% for fatigue, 40% for musculoskeletal pain, and 37% for concentration problems. Other commonly reported symptoms included skin reactions (42%) and weight gain (24%). The proportion of overweight/obese patients was 52%. Half of all respondents requested more information regarding PE. Patients with CML preferred individual training (82%), located outdoors (71%), at home (47%), or in an indoor swimming pool (31%). Regarding the training frequency, sports-inactive patients preferred a frequency of 1–2 training sessions per week, whereas sports-active patients preferred 3–4 sessions per week (p <0.001). Sports-inactive patients preferred a training time of 15–45 minutes, while sports-active patients preferred 30–60 minutes (p = 0.002). Subsequently, PE recommendations were developed for patients with CML. Combined resistance and endurance training (moderate intensity twice per week for 30 minutes) was recommended for beginners. Obese patients should prioritize joint-relieving sports. To reduce the risk of skin reactions, direct sunlight and possibly water sports should be avoided, and UV protection should be used. Conclusion: Counseling and motivation of CML patients to be physically active should be part of the standard of care as well as support for implementation.